catena-Poly[[[diaquacopper(II)]-bis[μ(2)-1,3-bis(1,2,4-triazol-1-yl)propane]] dinitrate monohydrate] - Feng, Wen (International Union of Crystallography, 2009)
The title Cu(II) coordination polymer, {[Cu(C(7)H(10)N(6))(2)(H(2)O)(2)](NO(3))(2)·H(2)O}(n), was obtained by the reaction of equimolar Cu(NO(3))(2)·4H(2)O and 1,3-bis(1,2,4-triazol-1-yl)propane (btp) in a water–methanol solvent. The Cu(II) atom is located on a centre of inversion and has an elongated octahedral coordination geometry formed by four N atoms from four symmetry-related btp ligands and two coordinated water molecules. Adjacent Cu(II) atoms are connected by btp ligands, generating a double-stranded chain. The nitrate anion is disordered over two positions in a 0.828 (7):0.172 (2) ratio.